Impact of Teacher Factors on Mathematics Performance of Lower Basic School Pupils in Lagos State - Iroko, Ganiyu Adisa; Malik, Nasrudeen Ayinde; Odekeye, Ola Tokunbo (Unib Press, 2024)
This study examined the teacher factors as a prognosticator of lower Basic school pupils' performance in Mathematics. 120 Mathematics teachers in Eight lower Basic schools were involved in the study. The research instrument used was a validated structured questionnaire using the Likert four-point measurement scale. The data collected were analysed using simple percentages and Chi-Square formula. The results of the study showed that teaching qualification has a significant effect on teachers' performance in Mathematics. It was revealed that teaching experience influences teachers' teaching process which directly improves teaching performance in class. In addition, subject mastery of lower Basic school Mathematics teachers highly influences their teaching performance which directly influences pupils' performance in Mathematics. Furthermore, the analysis displayed that teachers' commitment has a significant influence on teaching performance in lower Basic schools. The study recommended that lower Basic school teachers be aware of the influence that their teaching experience and academic qualification on their teaching performance and the performance of pupils. Also, education policy makers are advised give adequate attention to teachers' qualification, work experience and mastery of subject of specialisation in education policy considering their influence on teaching process in lower Basic school environments.